146 Glucagon-like peptide-1 analogues exert differential in vitro actions on macrophages and cardiac fibroblasts in experimental diabetes. (June 2018) - Abudalo, Rawan; Edgar, Kevin; O'Neill, Karla; Grieve, David; Green, Brian
Abstract : Background: The pathophysiological link between diabetes and cardiovascular disease is complex with compelling evidence indicating that hyperglycaemia, as a hallmark of diabetes, induces cardiac abnormalities specifically associated with inflammation, extracellular matrix (ECM) changes, and diastolic dysfunction, which accelerate heart failure development and progression. Glucagon-like peptide (GLP-1) is an incretin hormone, which confers proven glycaemic control in diabetes, and also demonstrates cardioprotective effects, which we have shown to specifically involve inflammation and ECM remodelling. The aim of this study was therefore to investigate precisely how GLP-1 exerts anti-inflammatory actions in experimental diabetes, directly comparing the effects of two GLP-1 analogues, exenatide and liraglutide, which have reported to confer differential clinical cardiovascular benefits. Methods: RAW 264.7 macrophages were exposed to normal (5.5 mM) or high glucose (25 mM) for 48–72 hour in the presence of exenatide or liraglutide (1 nM) to assess their anti-inflammatory effects on cell and secreted cytokine expression (real-time RT-PCR, proteome array). Effects on paracrine signalling were interrogated by incubating conditioned media from exenatide/liraglutide and/or glucose-treated macrophages with primary mouse cardiac fibroblasts prior to assessment of myofibroblast markers (real-time RT-PCR). Results: Mouse macrophages, but not cardiac fibroblasts, were confirmed to express the GLP-1 receptor. Interestingly, exenatide and liraglutide exerted differential effects on macrophage cytokine expression under normoglycaemic (e.g. TGF-β: exenatide 0.81±0.13, liraglutide 2.04±0.40; n=3, p<0.05) but not hyperglycaemic conditions. In contrast, cytokine/chemokine secretion was unaltered in normal glucose but decreased to a greater extent by liraglutide versus exenatide in high glucose (e.g. CXCL10, TNF-α, CCL12; n=3 pooled samples), whilst liraglutide suppressed high glucose-induced cardiac fibroblast differentiation more than exenatide (α-SMA, procollagen IαI), which was unaltered by normal glucose. Conclusions: Taken together, these results indicate that GLP-1 analogues, exenatide and liraglutide, exert differential actions on in vitro macrophage cytokine/chemokine expression and paracrine signalling, which may at least partly explain the reported differential cardiovascular benefits of these glycaemic agents in clinical diabetes.